Indeks Nilai Penting dan Keanekaragaman Komunitas Vegetasi Penyusun Hutan di Alas Burno SUBKPH Lumajang - Rawana; Wijayani, Suprih; Masrur, Muhammad Aqib (Jurnal Wana Tropika, 2022)
The importance value index and diversity are important indicators to determine the dynamics and stability of the vegetation community. The objectives of the study were (1) to determine the importance value index of seedlings, saplings, poles and trees composing the Bruno Forest community in SUBKPH Lumajang (2) to know the diversity of seedlings, saplings, poles and trees composing the Bruno Forest community in SUBKPH Lumajang. The research was conducted in the Bruno Forest Area, SUBKPH Lumajang, East Java. The plot method was used in this study with nested plots measuring 2x2m2 for seedlings, 5x5m2 for saplings, 10x10m2 for poles, and 20x20m2 for trees. The number of samples was 30 plots placed systematically, with a distance between plots of 20m. The conclusions of this study are (1) the forest vegetation community of Bruno Forest area is composed of 9 species belonging to 6 families, at tree level dominated by Pinus merkusii, at pole level by Swietenia macrophylla species, saplings and seedling level dominated by Calliandra surinamensis (2) Diversity at tree and pole level was categorized as high while at sapling and seedling level was categorized as moderate. The species evenness index at the tree, pole and saplling level was categorized as high, while at the seedling level it was categorized as medium.